The Influence of Leverage, Debt Default, Company Size, and the Previous Year's Audit Opinion on the Acceptance of Going Concern Audit Opinions - Aldhanarisha Aldhanarisha; Yudhi Herliansyah (International Journal Labs, 2023)
This study investigates the factors influencing the acceptance of going concern audit opinions, focusing on leverage, debt default, company size, and the preceding year's audit opinion. The research is based on the financial reports of 38 manufacturing companies listed on the Indonesia Stock Exchange (BEI), spanning a period of 5 years. Employing a purposive sampling method, logistic regression analysis is applied to assess the impact of these variables. The findings for the period 2017-2021 indicate that debt default, company size, and the previous year's audit opinion play a significant role in influencing the acceptance of going concern audit opinions. However, leverage does not exhibit a statistically significant effect on the acceptance of such opinions during this period. Contrastingly, the results for the years 2020-2021 reveal that the previous year's audit opinion is the sole influential factor affecting the acceptance of going-concern audit opinions. Leverage, debt default, and company size do not demonstrate a significant impact on the acceptance of going concern audit opinions during this specific timeframe. This research contributes valuable insights into the dynamics shaping the acceptance of going concern audit opinions, shedding light on the nuanced interplay of financial variables within the context of manufacturing companies listed on the Indonesia Stock Exchange.